2000
DOI: 10.1002/1096-8628(20001218)95:5<411::aid-ajmg1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Possible isochromosome 22 leading to trisomy 22

Abstract: We describe the first case of trisomy 22 resulting from a monocentric, possible isochromosome 22. The female infant had multiple anomalies including an abnormal face, ambiguous genitalia, and both ventricular and atrial septal defects. Survival was short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…There was no cleft lip, although the upper lip was carp‐shaped. The facial appearance bore a striking resemblance to the baby reported by Manasse et al [2000].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…There was no cleft lip, although the upper lip was carp‐shaped. The facial appearance bore a striking resemblance to the baby reported by Manasse et al [2000].…”
Section: Discussionsupporting
confidence: 53%
“…Recently, Manasse et al [2000] reported a female infant with trisomy 22 due to a possible isochromosome 22. The infant had multiple congenital abnormalities and survived for 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report a case of complete non‐mosaic trisomy 22 and review the natural history of those reported liveborn in the last 20 years [Petersen et al, 1987; Vohra et al, 1987; Voiculescu et al, 1987; Kukolich et al, 1989; Antle et al, 1990; McPherson and Stetka, 1990; Phillipson et al, 1990; Sundareshan et al, 1990; Feret et al, 1991; Kim et al, 1992; Lean et al, 1992; Kobrynski et al, 1993; Slater et al, 1993; Stratton et al, 1993; Fahmi et al, 1994; Golombek and Shaw, 1994; Nicholl et al, 1994; Bacino et al, 1995; Ladonne et al, 1996; Manasse et al, 2000]. The importance of recognizing the features of this syndrome and its natural history is highlighted so that appropriate counseling can be given at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%